Food Addiction in Gambling Disorder: Frequency and Clinical Outcomes - Jiménez-Murcia, Susana; Granero, Roser; Wolz, Ines; Baño, Marta; Mestre-Bach, Gemma; Steward, Trevor; Agüera, Zaida; Hinney, Anke; Diéguez, Carlos; Casanueva, Felipe F.; Gearhardt, Ashley N.; Hakansson, Anders; et al. (Frontiers in Psychology, 2017)
Background: The food addiction (FA) model is receiving increasing interest from the scientific community. Available empirical evidence suggests that this condition may play an important role in the development and course of physical and mental health conditions such as obesity, eating disorders and other addictive behaviors. However, no epidemiological data exist on the comorbidity of FA and gambling disorder (GD), or on the phenotype for the co-occurrence of GD+FA. Objectives: To determine the frequency of the comorbid condition GD+FA, to assess whether this comorbidity features a unique clinical profile compared to GD without FA, and to generate predictive models for the presence of FA in a GD sample. Method: Data correspond to N=458 treatment-seeking patients who met criteria for GD in a hospital unit specialized in behavioral addictions. Results: Point prevalence for FA diagnosis was 9.2%. A higher ratio of FA was found in women (30.5%) compared to men (6.0%). Lower FA prevalence was associated with older age. Patients with high FA scores were characterized by worse psychological state, and the risk of a FA diagnosis was increased in patients with high scores in the personality traits harm avoidance and self-transcendence, and low scores in cooperativeness (R2=0.18). Conclusion: The co-occurrence of FA in treatment-seeking GD patients is related to poorer emotional and psychological states. GD treatment interventions and related behavioral addictions should consider potential associations with problematic eating behavior and aim to include techniques that aid patients in better managing this behavior.